Degradation kinetic study of lysine in lysine hydrochloride solutions for injection by determining its main degradation product - Mengying Tao; Meng Zhu; Chunnuan Wu; Zhonggui He (Elsevier, 2015)
A limited number of researches have been reported to apply the Arrhenius equation to study the relationship between drugs and its degradation products so far. In the present work, the thermal degradation kinetics of lysine hydrochloride solutions for injection, the special solvent for ademetionine 1, 4-butanedisulfonate (SAM) for injection, was investigated at selected temperatures and pH values. The main degradation product of lysine was separated, purified, and confirmed as lysine lactam. A reversed-phase high performance liquid chromatographic (RP-HPLC) method without derivation was developed for the simultaneous determination of lysine and lysine lactam. The results confirmed that both the lysine degradation and lysine lactam generation followed zero-order reaction kinetics. The degradation and generation rate constants increased with increasing temperatures and decreasing pH values. The temperature-dependent degradation and generation reaction could be sufficiently modeled on the Arrhenius equation with the activation energy of 80.14 and 83.22 kJ/mol, respectively. Meanwhile, a linear relationship existed between the amount of lysine degradation and lysine lactam generation since the approximate activation energy. Considering there could be other side effects, we established an upper limit of lysine lactam (500 μg/ml), as the acceptable criteria for stability to estimate the shelf life together with lysine, which made the prediction more accurate and credible. Extrapolation data demonstrated that the lysine hydrochloride solutions for injection could be stable for two years stored at room temperature.